Determinant of the Corporate Social Responsibility (CSR) Disclosure at Mining Company - Arfan Ikhsan; Muhamad Yamin Noch; Ngatemin Ngatemin; Meilaty Finthariasari; Azizul Kholis (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
Research tries to test the effect deferred exploration and development, profitability, and solvency on CSR disclosure (CSRD). Population research are all registered mining company on the Indonesia Stock Exchange (ISE) from 2017 to 2020. Eleven companies according to the sample criteria of this research with purposive sampling technique. The results research summarize that BEPT and DAR, partially, do not affect the scope of CSRD with significant values of 0.594 and 0.089. Besides that, ROA variable has partial effect on ​​CSR disclosure with a significant value 0.048. Based on the test, it found that BEPT, ROA, and DAR was affect to the extent of CSR disclosure in mining companies with a significant value of 0.014. This research concludes that BEPT and DAR do not positively effect on CSR disclosure, while ROA affects to extent of CSR disclosure.